Les pratiques commerciales dans une région frontalière. Les exemples d’Arlon, de Luxembourg-ville et de Metz - Smits, Florence (Belgeo, 2006)
Abstract: „Parts of Belgium, France, Germany and Luxembourg which comprise the Great Region have witnessed an increase in the mobility of workers and in the degree of political collaboration. Nevertheless, this evolution does not seem to have had an impact on the consumption habits of workers who tend to remain quite different in Arlon, Luxembourg and Metz. In contrast, people with less mobility but more time available, such as the retired and young, seem to exhibit the same pattern of consumption.“
Keywords: Arlon; Einkaufen; Grenzarbeitnehmer; Handel; Luxemburg (Stadt); Metz; Mobilität; Verbrauch

Des Deutschtums fernster Westen. Eupen-Malmedy, die deutschen Dialekte redenden Gemeinden um Arlon und Montzen und die „Westforschung“ - Lejeune, Carlo (Griff nach dem Westen. Die „Westforschung“ der völkisch-nationalen Wissenschaften zum nordwesteuropäischen Raum (1919–1960), 2003)
Keywords: Arlon; Deutsch; Eupen; Malmedy; Montzen; Ostbelgien; Sprachgrenze; Westeuropaforschung